Regulating contracts according to the 2016 amendment to the French Civil Code - an analytical study compared to the position of the Iraqi legislator - إبراهيم خلف مدرس مساعد موج (Journal of Law and Political Science College, 2023)
the civil law regulates legal relations between people in general, and reflects the needs of individuals and society alike, and in light of the development taking place in the field of legal relations and the impact of the French civil law on legislative changes related to its neighboring countries and a desire to unify its law with the laws of countries The European Union has tended to amend some provisions related to contracts and their legal organization, which revolutionized the field of legal research and studies. Therefore, the most prominent features of the legislative change must be clarified, as well as the justifications and reasons that prompted the French legislator to adopt these amendments. And the search for the most important aspects of the legislative amendments that affected the provisions of contracts in comparison with the position of the Iraqi legislator by asking questions and clarifying the pros and cons of this amendment, as well as studying the extent of the efficacy of these legislations at the level of the French and Arab arena, including our country, Iraq.